The role of the International Criminal Police Organization in Iraq in the context of extradition - Jabbar khalaf , Ammar; Jabbar kredi AL-Qadi , Prof.Dr.Ail (Basra studies journal, 2022)
The International criminal police organization is a police and global organizations that actively contributes to activating the procedures of international police cooperation between the member states of the organization through its central offices in the member states of the organization through its central office in the member states of organization. It includes the Iraqi central office of Interpol ,which was established after the accession of the state of Iraq to the International criminal police organization in 1967,at the 36th session of the General Assembly of the International organizational in Tokyo, Japan . The accession agreement was ratified under Law No.204 of 1957 and the Iraq central office for Interpol exercises of its functions in cases of receipt and extradition of criminals from Iraq and other countries in coordination with the General Secretariat of the International Criminal police organization in this scope ,he has various activities in the extradition of criminals ,foreign militants, and dowry money and antiquities